Kharkiv incoherent scatter facility - Domnin, I. F.; Chepurnyy, Ya. M.; Emelyanov, L. Ya.; Chernyaev, S. V.; Kononenko, A. F.; Kotov, D. V.; Bogomaz, O. V.; Iskra, D. A. (НТУ "ХПІ", 2014)
The structure, parameters and operating modes of the incoherent scatter radar of the Institute of Ionosphere, Kharkiv are presented. Some results of the ionosphere research obtained by this facility are shown.

Наведено структуру, параметри і режими роботи радара некогерентного розсіяння Інституту іоносфери (м. Харків). Показано деякі результати спостережень іоносфери за допомогою цього обладнання.
Keywords: incoherent scatter radar; ionosonde; ionospheric observatory; ionospheric parameters; incoherent scatter method; радар некогерентного розсіяння; іонозонд; іоносферна обсерваторія; параметри іоносфери; метод некогерентного розсіяння радіохвиль